Drug Calculation Cards and Medication Errors in the Neonatal Intensive Care Units - Kazemkhanloo, Maryam; Nourian, Manijeh; Tajalli, Saleheh; Rassuli, Maryam; Salmani, Fateme; Fallahi, Minoo (Advances in Nursing & Midwifery, 2020)
Introduction: Medication administration errors are the most common medication errors. One of the most important causes of medication administration errors is a mistake in calculating the dose of medication by nurses. This study was conducted to evaluate the effects of using the Drug Calculation Cards on the amount and type of medication administration errors in the Neonatal Intensive Care Units (NICUs). Methods: This quasi-experimental study was conducted with one-group before-after design to examine the effects of using the Drug Calculation Cards on the amount and type of medication administration errors. Eligible NICU nurses in selected centers affiliated to Qazvin University of Medical Sciences were registered (n = 33) in the study within three months. Then, before intervention data were collected using “medication administration errors reporting” questionnaire. Three months later the intervention (drug calculation card) was done and the same medication administration errors reporting questionnaire was dispersed. The data were entered to the SPSS version 14 and was analyzed using descriptive statistics. Results: The mean medication administration error during the three months before and three months after the intervention were 12.41 ± 14.48 and 9.62 ± 12.72, respectively, which had a statistically significant difference (P = 0.004). Conclusions: Using the Drug Calculation Cards by nurses in